Urgency of digitizing school libraries in Indonesia’s post-truth era: A cross-perspective review - Syifaun Nafisah (Universitas Padjadjaran, 2022)
The pandemic era has changed all aspects of human activity to be online-based, including the learning process. The online learning process requires digital-based learning resources and knowledge. The condition of school libraries in Indonesia, which is still in the library automation system stage, causes the library's role as a center of knowledge to be not optimal. Therefore, this study examined the urgency of digitizing school libraries to create learning centers based on various perspectives. This study used a qualitative approach with a literature review type. The validity and reliability test used used cross-reference source checks, quick recording, member checks, and extended observation. Data analysis used content analysis with the Miles and Huberman approach model. Based on legal, psychological, health, educational, economic, social, and technological perspectives, research showed the urgency of digitizing school libraries in the post-truth era. Library digitalization has created an educational space allowing the learning process in the library through the provision of collection resources in digital collections by the library. Schools face obstacles in digitizing libraries: inadequate facilities and infrastructure, lack of skills and abilities of librarians for digitization, lack of support from schools as institutions that oversee libraries, and lack of funds provided. Libraries need to consider barriers and solutions. If realized, the library can become a knowledge center as the primary source of information providing the required information, especially for school-age users.